Dual contribution of surface charge and protein-binding affinity to the cytotoxicity of polystyrene nanoparticles in nonphagocytic A549 cells and phagocytic THP-1 cells. Issue 20 (17th October 2016) - Hwang, Sung-Hyun; Thielbeer, Frank; Jeong, Jiyoung; Han, Youngju; Chankeshwara, Sunay V.; Bradley, Mark; Cho, Wan-Seob
ABSTRACT: Knowledge that links the physicochemical properties of nanoparticles (NP) to their toxicity is key to evaluating and understanding mechanisms underlying toxicity and developing appropriate testing methods for NP; however, this is currently limited since only a small set of NP have been used, with typically poor control of their physical properties. In this study, eight types of polystyrene NP (PLNP) were synthesized with different functional groups, but all based on an identical core. In vitro cell-based assays were performed to determine the influence of changes in physicochemical properties, such as charge, hydrodynamic size, and protein binding potential, in relation to NP-mediated toxicity. The PLNP were incubated with nonphagocytic A549 cells or phagocytic differentiated THP-1 cells for 4 h with/without fetal bovine serum (FBS), followed by incubation for 20 h in FBS-supplemented medium with/without a washing step, to assess cell-type specificity and impact of protein corona formation. The effect of surface charge on cytotoxicity differed between A549 cells and THP-1 cells. In nonphagocytic A549 cells, the zeta potential of PLNP exhibited a negative correlation with cytotoxicity, partly due to the level of coronated protein that might affect cellular uptake. In phagocytic THP-1 cells, the zeta potential of PLNP showed a positive correlation with cytotoxicity but coronated protein levels displayed no marked association with cytotoxicity, owing to the professional uptake efficacy of phagocytic cells. The consistency of our data with THP-1 cells with the surface charge paradigm in nanotoxicology suggests that phagocytic cells are the predominant targets for lung inflammatory reactions induced by PLNP.